Influence of coronal mass ejections on global electric circuit - Kumar, C.P. Anil; Panneerselvam, C.; Nair, K.U.; Selvaraj, C.; Gurubaran, S.; Rajaram, R.; Jeeva, K. (2008)
This paper is concerned with the elucidation of flow of particles and field from the sun into the terrestrial system and their subsequent role in Global Electric Circuit (GEC). Many flare associated Coronal Mass Ejections (CMEs) have been studied from ACE satellite data during the last phase of the 23rd solar cycle. Such solar ejections consist of hot electrons, protons and helium ions embedded in magnetic fields of various intensities and which travel with velocities greater than supersonic speed towards the earth and breach terrestrial magnetic fields (under favourable conditions) and cause geomagnetic storms. Contemporary data of geoelectrical measurements made at the high latitude Indian Antarctic Research Station, Maitri (70.45°S, 11.44°E) have also been used to investigate the electrical processes during, before and after the above events. The study leads to the conclusion that CMEs enhance the population of the multi-ion plasma species, which paves the way for an increase in the overhead ionospheric electric potential during the onset or even up to the main phase of the magnetic disturbance. The near earth electrical environment is besieged with magnetic disturbance at the high latitude.